Keterampilan Menyimak Teks Prosedur Melalui Teknologi Informasi “Tik-Tok” - Wahyu Dini Septiari (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
Listening skills for some teachers are more on listening skills, not on listening as a process and mechanics so that skills in technological sophistication are needed as interesting learning media. Technology can be used to help students develop listening skills through information technology, one of which is